2021
DOI: 10.3389/fonc.2021.645745
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Adenoviral p53 Gene Therapy Clinical Trials in Recurrent Head and Neck Squamous Cell Carcinoma

Abstract: BackgroundWe conducted an analysis of previous adenoviral p53 (Ad-p53) treatment data in recurrent head and neck squamous cell carcinoma (HNSCC) patients to identify optimal Ad-p53 treatment methods for future clinical trials.MethodsThe analysis involved recurrent HNSCC patients treated with Ad-p53 for whom p53 genotyping and immunohistochemistry tumor biomarker studies had been performed (n = 70). Ad-p53 tumor treatment responses defined by RECIST 1.1 criteria were correlated with Ad-p53 dose and tumor p53 bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“… 250 In preclinical studies, a p53 -armed adenoviral vector (Ad-p53), alone or combined with PD1 blockade, showed an enhanced control of local treated and distant untreated tumors compared with anti-PD1 alone, suggesting that Ad-p53 immunotherapy mediates abscopal effects and can reverse resistance to ICI. 249 , 251 , 252 These results encouraged the clinical evaluation of Ad-p53 in combination with PD1 blockade. Along this line, the Phase I–II investigation NCT02842125 aimed at evaluating the safety and efficacy of i.t .…”
Section: Other Virus-based Immunotherapiesmentioning
confidence: 95%
“… 250 In preclinical studies, a p53 -armed adenoviral vector (Ad-p53), alone or combined with PD1 blockade, showed an enhanced control of local treated and distant untreated tumors compared with anti-PD1 alone, suggesting that Ad-p53 immunotherapy mediates abscopal effects and can reverse resistance to ICI. 249 , 251 , 252 These results encouraged the clinical evaluation of Ad-p53 in combination with PD1 blockade. Along this line, the Phase I–II investigation NCT02842125 aimed at evaluating the safety and efficacy of i.t .…”
Section: Other Virus-based Immunotherapiesmentioning
confidence: 95%
“…A Phase 2 trial [NCT03544723] is ongoing to investigate the combination of gendicine with clinicians’ choice of ICIs. Preliminary gene expression analysis comparing pre- and post- gendicine-treated HNC tumor revealed upregulation of IFNγ-signaling genes, decreased TGF-β and β-catenin signaling ( 74 ) and increased CD8+ T cells signature, which is associated with increased clinical responses to ICIs ( 74 ).…”
Section: Targeted Agents Tested In Combination With Icis In Hncmentioning
confidence: 99%
“…A Phase III clinical trial for use of Advexin (adenovirus containing TP53) (INGN 201, Ad5CMV-p53) versus methotrexate in treating advanced recurrent HNSCC showed that patients with wild-type p53 had better response to Advexin, whereas patients carrying mutant p53 were more responsive to methotrexate chemotherapy which indicates the potential of p53 as a biomarker to design a targeted therapy [141]. This approach has subsequently been used in a Phase II trial (NCT03544723) investigating safety and efficacy of p53 gene therapy combined with immune checkpoint inhibitors in solid tumours including HNSCC [142]. Previous Ad-p53 clinical trials appear to have been negatively impacted by the inclusion of patients with unfavourable p53 biomarker profiles and by under dosing of Ad-p53 treatment [142].…”
Section: Tp53/rbmentioning
confidence: 99%
“…This approach has subsequently been used in a Phase II trial (NCT03544723) investigating safety and efficacy of p53 gene therapy combined with immune checkpoint inhibitors in solid tumours including HNSCC [142]. Previous Ad-p53 clinical trials appear to have been negatively impacted by the inclusion of patients with unfavourable p53 biomarker profiles and by under dosing of Ad-p53 treatment [142]. This has important implications for Ad-p53 gene therapy and future p53-targeted therapy.…”
Section: Tp53/rbmentioning
confidence: 99%